Work worlds and gender relations: contributions and challenges of an interdisciplinary study agenda - Garazi, Débora; Gómez Molla, Rosario (Centro Interdisciplinario de Investigaciones en Género. IdIHCS (CONICET - UNLP). Facultad de Humanidades y Ciencias de la Educación, Universidad Nacional de La Plata, 2021)
The introduction to the dossier addresses some classic academic-political problems within the interdisciplinary field that studies the world of work and gender relations. In the first section, we briefly reconstruct how this field of studies was created. In the second, we identify three problematic nodes of the feminist agenda: discussions on the social organization of work, within which domestic and care work plays a leading role; the processes of gendered and hierarchical professions and the different ways in which the State has intervened on issues related to work and gender. Finally, we refer to the “gaps” that, we understand, still exist in this field of studies.